Numerical Analysis of Dark Currents in T2SL nBn Detector Grown by MBE on GaAs Substrate - Małgorzata Kopytko; Emilia Gomółka; Tetiana Manyk; Krystian Michalczewski; Łukasz Kubiszyn; Jarosław Rutkowski; Piotr Martyniuk (Proceedings, 2019)
The paper presents the numerical analysis of the performance of the nBn type-II superlattice barrier detector operated at 230 K. Results of theoretical predictions were compared to the experimental data for the nBn detector composed of AlAs0.15Sb0.85 barrier and InAs (5.096 nm)/InAs0.62Sb0.38 (1.94 nm) superlattice absorber and contact layer. Detector structure was grown on GaAs substrate using molecular beam epitaxy. To determine the position of the electron miniband and the first heavy hole state in the superlattice, we have used a k·p model which can also predict the absorption spectrum and the cut-off wavelength of an absorber layer. As shown, the most important parameters in the nBn structure optimization is the barrier height in the valence band. While the barrier in the conduction band must be high enough to prevent the flow of the electron current from the contact layer to the absorber, the barrier in the valence band must be sufficiently low to ensure the flow and a collection of optically generated holes. The position of the valence band edge for the AlAsSb barrier was changed by changing the valence band bowing parameter for this ternary material. Proper fit of the calculated plot to our experimental data was obtained assuming no bowing in the valence band for AlAsSb barrier.